2014
DOI: 10.1371/journal.pone.0089663
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1A/1B Receptors as Targets for Optimizing Pigmentary Responses in C57BL/6 Mouse Skin to Stress

Abstract: Stress has been reported to induce alterations of skin pigmentary response. Acute stress is associated with increased turnover of serotonin (5-hydroxytryptamine; 5-HT) whereas chronic stress causes a decrease. 5-HT receptors have been detected in pigment cells, indicating their role in skin pigmentation. To ascertain the precise role of 5-HT in stress-induced pigmentary responses, C57BL/6 mice were subjected to chronic restraint stress and chronic unpredictable mild stress (CRS and CUMS, two models of chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 72 publications
2
42
0
1
Order By: Relevance
“…It has been reported that 5‐HT can induce melanogenesis and mammalian skin can both synthesize and metabolize 5‐HT . LC‐MS assay of 5‐HT in both serum and skin revealed that in mice serum, 5‐HT levels were down‐regulated in both CRS and CUMS groups with no significant differences.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…It has been reported that 5‐HT can induce melanogenesis and mammalian skin can both synthesize and metabolize 5‐HT . LC‐MS assay of 5‐HT in both serum and skin revealed that in mice serum, 5‐HT levels were down‐regulated in both CRS and CUMS groups with no significant differences.…”
Section: Resultsmentioning
confidence: 93%
“…Six‐ to seven‐week old, male, C57BL/6 mice which are in telogen stage, with profound stress response, were found to be suitable for the study and obtained from Shanghai laboratory animal centre, China. As per standard procedures, all mice were acclimated for a week at a 22±1°C temperature and 50±5% humidity with a 12‐hour light/dark cycle (lights on at 6:00 am and off at 18:00 pm ). During this period, food and water were provided ad libitum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17) It has been reported that interferon-γ (IFN-γ) is highly expressed in the lesions of vitiligo patients. Furthermore, UVB irradiation can induce the secretion of IFN-γ in keratinocytes or macrophages.…”
Section: )mentioning
confidence: 99%
“…16) Our preliminary study also found that 5-HT 1A receptor took a vital part in 'brain-skin connection' to regulate skin pigmentation. 17) It has been reported that interferon-γ (IFN-γ) is highly expressed in the lesions of vitiligo patients. Furthermore, UVB irradiation can induce the secretion of IFN-γ in keratinocytes or macrophages.…”
mentioning
confidence: 99%